2005
DOI: 10.1063/1.2130889
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs quantum wells on wafer-bonded InP∕GaAs substrates

Abstract: Wafer bonding and hydrogen implantation exfoliation techniques have been used to fabricate a thin InP template layer on GaAs with intermediate silicon nitride bonding layers. This template layer was used to directly compare subsequent metal organic vapor phase epitaxial growth of InGaAs∕InAlAs quantum-well structures on these wafer-bonded templates to growth on a standard InP substrate. Chemical mechanical polishing of the bonded structure and companion InP substrates was assessed. No effects from the coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…However, previous work with InP has shown that the removal rate is on the order of 10 nm/minute [9] and the results here are consistent with that value. The ability to controllably polish exfoliated layers using these CMP parameters is demonstrated on an exfoliated InP layer that was transferred to a different substrate (GaAs in this case).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…However, previous work with InP has shown that the removal rate is on the order of 10 nm/minute [9] and the results here are consistent with that value. The ability to controllably polish exfoliated layers using these CMP parameters is demonstrated on an exfoliated InP layer that was transferred to a different substrate (GaAs in this case).…”
Section: Resultssupporting
confidence: 94%
“…This is particularly useful for the CMP of wafer bonding and layer transfer schemes, where submicron layers need to be planarized. [9] These results provide a scientific and quantitative basis for CMP of III-V exfoliated layers beyond the more typically mentioned and less …”
Section: Discussionmentioning
confidence: 93%
“…In the case of ion-cutting (or Smart CutTM) process based on wafer bonding and hydrogeninduced layer exfoliation, it is common to transfer III-V layers onto Si. The transferred structure is then used as a template for subsequent epitaxial re-growth of device structures [3][4][5]. Due to the rough as-transferred surface and considerable implantation-induced radiation damage near the surface region of transferred structure, a chemical mechanical polishing (CMP) process and/or other surface treatments are required before re-growth.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] InP-based photodetectors and lasers on Si substrates are particularly of interest for optical interconnection purposes since their optical spectra can cover low dispersion and minimum loss wavelengths for optical fiber communications at 1.35 and 1.55 m. 4 To overcome the difficulty of epitaxial growth caused by lattice mismatch between different materials, wafer bonding has been utilized for integration of III-V materials with Si. 4,6,7 Before the regrowth of epitaxial layers, a chemical mechanical polishing is usually required for improving the as-transferred III-V surface flatness and removing the residual hydrogen implantation-induced damage near the surface region. 5 The obtained III-V-on-Si structures have been used as templates for subsequent epitaxial growth of device structures.…”
mentioning
confidence: 99%
“…Recently the ion-cut process ͑or Smart-cut®͒ based on hydrogen ion implantation and wafer bonding has been used to integrate III-V layers on Si. [6][7][8] Recently we demonstrated a high quality III-V layer transfer scheme that combines ion cutting together with selective chemical etching. 4,6,7 Before the regrowth of epitaxial layers, a chemical mechanical polishing is usually required for improving the as-transferred III-V surface flatness and removing the residual hydrogen implantation-induced damage near the surface region.…”
mentioning
confidence: 99%